Increase in takeover protection and firm knowledge accumulation strategy - Wang, Heli; Zhao, Shan; He, Jinyu (Strategic Management Journal, 2016)
Research summary : We argue that the extent to which a firm faces takeover threats affects its knowledge structure. In particular, takeover threats may lead to managers' reluctance to adopt a strategy toward firm‐specific knowledge accumulation because implementing this strategy requires them to acquire specialized skills, which are at risk under takeover threats. Conversely, takeover protection leads to an increase in firm‐specific knowledge. Further, the relationship between takeover protection and firm‐specific knowledge is positively moderated by managerial ownership, which helps align managerial interests with those of shareholders. But the relationship is negatively moderated by managerial tenure, as long‐tenured managers have already committed to their firms. Using a differences‐in‐differences method with D elaware antitakeover rulings in the mid‐1990s as an exogenous shock, we found results supporting these arguments . Managerial summary : We examined how changes in the D elaware antitakeover rulings in mid‐1990s affected the knowledge structure of firms incorporated in D elaware. We reasoned that with a greater level of takeover protection, top managers of those firms incorporated in D elaware felt higher job security, thus providing them stronger incentives to make strategic decisions toward the development of firm‐specific knowledge and to make corresponding human capital investments in specialized skills. Empirically, firms incorporated in D elaware were found to have an increase in the level of firm‐specific knowledge in their knowledge structure after the mid‐1990s. Furthermore, our analysis suggests that the role of takeover protection on top manager incentives is particularly salient when the managers are awarded with more company shares and when the managers have shorter organizational tenure . Copyright © 2015 John Wiley & Sons, Ltd.